487 The Human Anti-Ganglioside GM1 Autoantibody Response Following Traumatic and Surgical Central Nervous System Insults. (1st April 2022) - Roukerd, Maryam R.; Schneider, Lonnie; Hawryluk, Gregory W. J.; Faulkner, Jenna; Reichert, Ethan; Flis, Alexandra; Abou-Al-Shaar, Hussam; Rubiano, Andres M.
Abstract : INTRODUCTION: The immune response to central nervous system (CNS) injuries has long been considered a significant contributor to secondary injury following neurotrauma however the autoimmune response to the normal immune-privileged CNS has been insufficiently considered. It has been identified as a possible pathomechanism underlying delayed dementias known to occur after TBI and SCI however the CNS-directed autoantibody response following CNS injury remains poorly understood and the autoimmune response following intra-axial brain surgery is unknown. METHODS: Nine serum samples were collected serially from 17 acute severe TBI, 22 acute SCI, and 24 intra-axial brain tumor resection patients for 30 days; 25 healthy subjects served as a control group. An ELISA assay quantitated IgG and IgM autoantibodies to ganglioside GM-1. The maximum autoantibody titers and their correlation with putative predictors such as age, gender, clinical and radiological measurements were investigated. RESULTS: Anti-GM1 IgG autoantibody titers were increased following SCI, TBI, and brain tumor resection as compared with baseline values and control patients. By contrast, anti-GM1 IgM autoantibody titers did not significantly change following insult nor show promise as a biomarker. The maximum IgG titers measured in the first 30 days were significantly increased in TBI patients (p<0.01), in SCI patients (p<0.01), and in brain tumor resection patients (p<0.05). The highest IgG titers (or peaks) were most commonly seen at day 14 post-insult in TBI and SCI patients while brain tumor patients did not demonstrate acute increases consistent with a peak. Higher GM1 IgG autoantibodies were associated with more severe insults. The Rotterdam score strongly correlated with increased IgG titers in TBI patients (p<0.05). Age and gender did not correlate with GM1 autoantibody titers in any of the types of insult we studied. CONCLUSION: These findings suggest that patients with diverse CNS insults are at risk for CNS-directed autoimmune responses and in particular those with more severe insults. These findings highlight the need to better understand the CNS-directed autoimmune response to insult, its clinical relevance and potential as a therapeutic target.